A finite element analysis approach to design and optimize the static structural impact on a skateboard - Abid, A.; Bhuiyan, A. A. (materialstoday: Proceedings, 2022)
Skateboarding is an extreme sport which has gained huge appreciation in recent times due to its flexibility, mobility, feasibility, environment friendliness, compact size and various conspicuous health benefits. With increasing appeal among the youth, the injuries that are associated with skateboarding sport are also ever on the rise. This upsurge of fatalities caused by skateboarding has largely been investigated in terms of aerodynamical impact, drag and lift, motion study and material preferences. This paper undertakes a novel approach to explore probable structural failure of a skateboard when a static load is applied. The numerical study appends the force as the load of a rider weighing 80 kg in mass with necessary boundary conditions and assumed zero load variation during the whole computational time. The truck and deck are the most sensitive parts when the skateboard is exposed to load impact due to weight. Three skateboard prototypes differing in their individual board`s thickness - are proposed in the paper to predict their structural failure under the given conditions. Other necessary conditions and assumptions remain same for all the three models. The static structural impact study shows discretized points of interest to investigate developed stress, resultant strain and deformation within each of the optimized prototypes. Von-mises stress is considered in order to get an overall idea of the stress along the skateboard structure and to calculate factor of safety (FOS) for each of the prototypes. Lastly, a comparative analysis of the calculated safety factor of each of the model is tabulated and the best performing prototype is brought forward for further research. Fidelity test of the working finite element method is executed to assess the authentication and sufficient convergence of the results are showed to produce outcomes with optimum accuracy. Relevant aerodynamic parameters and dynamic impacts around the skateboard are ignored in order to simplify the structural impact analysis.